Inhaled Steroids: First Line Treatment of Adult Asthma - André Cartier (Canadian Respiratory Journal)
Corticosteroids are the most potent inhaled anti-inflammatory drugs for asthma treatment. This paper reviews the clinical evidence supporting the early use of inhaled steroids in asthma as a first line treatment. Inhaled steroids can probably alter the course of asthma, especially in mild asthmatics. Once they have been shown to improve control of asthma and even if the need for beta2-agonists is virtually nil, their use should be continued at low doses (ie, equivalent to 400 to 500 μg of budesonide or beclomethasone) for at least one year before attempting to reduce the dosage.